Low-complexity detection method for spatial modulation based on M-algorithm - Zheng, Jianhong; Yang, Xiaobo; Li, Zhe (Electronics letters, 2014)
A novel M-algorithm-based detection method called M-algorithm to maximum likelihood (M–ML) is proposed for spatial modulation. The proposed algorithm has fixed complexity and reduces complexity by using a parallel structure to limit the search space of an optimum decoder. The simulation results show that by carefully choosing proper values of M, the new algorithm can reduce the computational complexity significantly while maintaining a near-optimum bit error rate performance.